Effect of tactile stimulation on the welfare of English Thoroughbred foals - Aguirre, Celina (2024)
The aim of this study was to evaluate the effect of tactile stimulation on the behaviour, physiological indicators, and performance of Thoroughbred foals. The experiment was conducted at Haras Cerro Punta, Chiriqui, Panama. Thirty-three foals with homogeneous weights were randomly assigned to three treatments: control (CON; n = 13), tactile stimulation (TS; n = 10), and tactile stimulation plus habituation to handling for 8 consecutive days (TS + HAB; n = 10). Tactile stimulation was performed 12 h after birth by massaging the entire body of the newborn for 45 min. Habituation to handling started the day after touch stimulation, 15 min per day for 8 consecutive days. Behaviour was assessed using escape distance and reactivity to containment during veterinary interventions on a 5-point scale (1-5). In addition, heart and respiratory rates and daily weight gain were determined in the first and fifth months of age. Analysis was performed using linear mixed or nonparametric tests. The escape distance did not differ between treatments (p>0.05). TS+HAB animals showed lower reactivity during restraint at both times compared to CON (p<0.05). The respiratory rate only differed between TS+HAB and CON at the first moment (p<0.05). However, there were no significant differences in daily weight gain between the treatments (p>0.05). It was concluded that the foals that received tactile stimulation and habituation to handling for eight consecutive days (TS + HAB) had consistently lower reactivity throughout the evaluated moments and a lower respiratory rate at one month of age.